Zoning based cascade infrastructure system design for urban waterlogging prevention. Issue 1 (July 2021) - Tian, Ziyang; Chu, Junying; Wang, Hao; Zhou, Zuhao
Abstract: With the development of global climate change and urbanization in China, urban waterlogging caused by rainstorm has a serious impact on the safety of people's life and property and the development of social and economic. Based on the hydraulic model, taking Xining City as an example, a set of multi-layer flood prevention infrastructure construction technology system is proposed, in which the microscale-drainage-system mainly includes the sponge transformation of building blocks, the construction of sponge park; the mesoscale-drainage-system mainly includes the transformation of pipe system for different return periods, the transformation of combined flow and separate flow system; the macroscale-drainage-system mainly includes utility tunnel system, natural and artificial storage facilities. Through quantitative evaluation of rainstorm with 50 year return period, under the construction of microscale-drainage-system and mesoscale-drainage-system with different return period index, the total drainage capacity increased from 1.407 million m 3 to 1.573 million m 3 and 1.830 million m 3 . The total accumulated water is 1.073 million m 3 and 0.816 million m 3 respectively, which are less than 1.173 million m 3 of macroscale-drainage-system new storage capacity.